Investigating Students’ Perception on the Impact of Song Lyrics in Improving Reading Comprehension at SMAN 5 Palu - Nabila, Putri; Mashuri, Mashuri; Lebagi, Desrin; Budi, Budi (Journal of English Language and Education, 2026)
This study aims to investigate the perceptions of students at SMAN 5 Palu regarding the impact of using song lyrics to improve English reading comprehension. This study focuses on the role of song lyrics in increasing reading motivation and the challenges faced by students in their use. Although reading comprehension is an essential skill, international assessment results such as PISA show that Indonesian students' reading literacy is still below the global average, causing students to often feel bored and have difficulty understanding conventional texts. This study used a descriptive qualitative design with 25 students from class X Merdeka 1 of SMAN 5 Palu selected through purposive sampling. Data were collected through open questionnaires and semi-structured interviews, then analyzed using Miles and Huberman's interactive model. The results showed that students had positive perceptions of the use of song lyrics. Song lyrics increase learning motivation through a fun and relaxed atmosphere, and help improve vocabulary, contextual meaning comprehension, and grasping main ideas. Challenges found include the use of slang, figurative meanings, fast pronunciation, and distractions for some students. This study concludes that song lyrics are effective authentic material in EFL reading learning.